Peran Lembaga Perlindungan Anak dalam Penanganan Kasus Kekerasan Seksual di Lingkungan Pendidikan Studi Kasus Pesantren di Kabupaten Agam - Sherlyn Novtrsiya Melati Putri; Khaila Humaira Ridwan; Asmak Ul Hosnah (Sharia Journal and Education Center Publishing, 2024)
Cases of sexual violence in Indonesia show a concerning trend, especially in the context of educational institutions. This research analyzes the role of DP3AP2KB and inter-agency coordination in handling sexual violence cases in the pesantren environment of Agam Regency. Using the normative juridical research method, this study examines the sexual violence case at MTI Canduang involving 43 students as victims. The research results show that DP3AP2KB performs a preventive function through socialization and education, as well as providing a 24-hour complaint service. In handling the case, there was effective coordination between three main institutions: Polresta Bukittinggi as law enforcement, the MTI Canduang Islamic boarding school which formed an internal investigation team and a legal team, and DP3AP2KB which provided psychological support. This multi-stakeholder coordination model successfully revealed an increase in the number of victims from 5 to 43 people and ensured comprehensive case handling from disclosure to victim support.